Intelligent systems applications - Gams, Matjaž (Informatica (Ljubljana), 2001)
In this paper we present and discuss the state of intelligent system applications, with special emphasis of Slovenia. We take the viewpoint that intelligent systems facilitate a new qualitative step towards the information society. Thus, they provide an important opportunity for any country to intensity its information, economic and social development. We present some intelligent system applications developed or being developed in our group: (1) EMA, an employment agent, (2) GIVE, a semantic web speaking system, and (3) DEXi, a decision modeling system. Based on past experience, we highlight the principal problems that occur in the development and exploitation of intelligent systems, and suggest improvements for the future.
Keywords: inteligentni informacijski sistemi; aplikacije; informacijska družba